Memory Decline and Behavioral Inflexibility in Aged Mice Are Correlated With Dysregulation of Protein Synthesis Capacity - Yang, Wenzhong; Zhou, Xueyan; Ma, Tao (Frontiers in Aging Neuroscience, 2019)
Understanding of the molecular mechanisms underlying age-associated cognitive impairments will not only contribute to our general knowledge about “aging” biology, but also provide insights for more effective strategies to prevent and improve the quality of life for both normal aging and pathological aging such as Alzheimer’s disease (AD). Here we first assessed and compared the performance of cognition and synaptic plasticity in young (3-5 month old) and aged c57BL/6J mice (19-21 months old). Findings from behavioral tests demonstrated that old mice, compared to young mice, displayed impairments in spatial learning/memory, recognition memory, and behavioral flexibility. Further, synaptic electrophysiology experiments on hippocampal slices revealed that early form of long-term potentiation (LTP, a synaptic model for memory formation) was inhibited in old mice. At the molecular level, biochemical assays on brain tissue showed dysregulation of signaling pathways controlling protein synthesis capacity including: up-regulation of AKT-mTORC1-p70S6K signaling, which is associated with translation of terminal oligopyrimidine (TOP) class of mRNAs that encode translational machinery; hyper-phosphorylation of mRNA translational elongation factor 2 (eEF2) and its upstream regulator AMP-activated protein kinase (AMPK), indicating repression of general protein synthesis. Moreover, young and old mice exhibited similar brain levels of translational initiation factor 2α (eIF2α) phosphorylation, which is known to be increased in AD and linked to the disease pathophysiology. Thus, our data provide evidence at the molecular level to highlight the similarity and difference between normal and pathological aging, which may contribute to future studies on diagnostic/prognostic biomarkers for aging-related dementia syndromes.